Conductive three-phase ultra-high performance concrete and preparation method thereof

By adding steel fiber, carbon fiber and conductive nano-carbon black into ultra-high performance concrete, the problem of balancing mechanical properties and conductive properties in ultra-high performance concrete is solved, and the connectivity of the conductive network and the improvement of mechanical properties are achieved. It is suitable for fields such as intelligent structural monitoring, electromagnetic shielding, grounding of power equipment, and road deicing and snow melting.

CN120647270APending Publication Date: 2025-09-16GUANGXI UNIV +6
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510819030.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-18
Publication Date
2025-09-16

AI Technical Summary

Technical Problem

Existing technologies make it difficult to simultaneously take into account mechanical properties and conductive properties in ultra-high performance concrete. Excessive steel fiber content leads to a decrease in mechanical properties, and insufficient conductive phase content in ordinary concrete leads to uneven conductive properties.

Method used

Conductive three-phase ultra-high performance concrete is prepared by adopting a three-phase composite method of steel fiber, carbon fiber and conductive nano-carbon black, with the specific proportions being 1.6-2.5 vol.% of steel fiber, 0.6-1.0 vol.% of carbon fiber and 0.7-1.0 wt.% of conductive nano-carbon black, through ultrasonic dispersion technology.

Benefits of technology

The conductive network connectivity and mechanical properties of concrete were significantly improved. The resistivity decreased by 99.85% after 28 days and hardly increased after 7 days. It has good application prospects in deicing and snow melting.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120647270A_ABST
    Figure CN120647270A_ABST
Patent Text Reader

Abstract

The invention provides conductive three-phase ultra-high performance concrete and a preparation method thereof. The steel fibers, the carbon fibers and the conductive nano carbon black are doped into the concrete, so that the construction performance, the mechanical performance and the electric heating performance of the concrete are considered; according to the invention, the steel fiber, the carbon fiber and the conductive nano carbon black are mixed, so that the expansion degree reduction amount and the mechanical property change amount can be approximately regarded as superposition of respective single-doping influence amounts; the reduction amount of resistivity caused by conductive three-phase mixing is far greater than the difference value between the UHPC matrix resistor and the conductive three-phase separately-doped resistor and the UHPC matrix parallel resistor, which means that the size effects of the three resistors are complementary to greatly increase the connectivity of the conductive network; the electrical resistivity of the UHPC at the 28d age is reduced by 99.85% compared with that of the UHPC at the element UHPC during the optimal mixing of the conductive three phases, the electrical resistivity is almost not increased after the 7d age, the temperature is increased by 54.9 DEG C after being electrified for 150min, and the deicing and snow melting application prospect is relatively good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of building materials, and in particular to a conductive three-phase ultra-high performance concrete and a preparation method thereof. Background Art

[0002] With the deepening of the concept of sustainable development, cement-based materials are continuously moving towards intelligent and diversified development. Among them, conductive cement-based materials, due to their excellent electrothermal, self-sensing, pressure-sensitive, and temperature-sensitive properties, are widely used in intelligent structural monitoring, electromagnetic shielding, power equipment grounding, cathodic protection of steel bars, and road de-icing and snow melting, becoming a research hotspot for the multifunctionalization of cement-based materials. Previous research on conductive concrete has typically been based on conventional concrete. Conventional concrete requires the addition of coarse aggregate during its preparation to ensure strength, but coarse aggregate has a high electrical resistivity and can be considered an insulating material. The addition of coarse aggregate can lead to problems such as interrupted conductive paths and uneven heating of the concrete. Furthermore, conventional concrete has a low matrix strength, and the high content of conductive phases can lead to a decrease in mechanical properties. Therefore, it is difficult for conventional concrete to achieve both mechanical and electrical properties.

[0003] Ultra-High Performance Concrete (UHPC), with its advantages of high elastic modulus, high strength, high durability, and high density, has been used in long-span bridge decks and pavements. Its ability to de-ice and melt snow on bridge decks during freezing weather is a critical societal need. Although the steel fibers in UHPC generally enhance its electrical conductivity compared to conventional concrete, conventional steel fiber dosages in UHPC preparations do not form dense, overlapping conductive pathways within the material. Excessive steel fiber dosages can lead to fiber clumping, which degrades the mechanical properties of UHPC. Furthermore, in the highly alkaline environment of the UHPC matrix, a passivation layer forms on the steel fiber surface, resulting in a long-term decrease in electrical conductivity. Therefore, the preparation of conductive UHPC using only steel fibers is not suitable. A rational combination of conductive phase materials of varying materials and sizes, synergistic with the steel fibers, is required to achieve UHPC with a balanced balance of ductility, compressive strength, tensile strength, and sufficiently low resistivity.

[0004] Currently, some research has examined the effects of adding multiple conductive phases to conventional concrete. Developed calculations have revealed the preparation of conductive concrete by adding carbon fiber and graphite. Results show a 10.09% increase in 28-day compressive strength compared to the baseline, significantly enhancing its electrical conductivity. Existing research has also reported the preparation of conductive concrete by adding steel fiber and graphite. Graphite has been found to significantly negatively impact the mechanical properties of conductive concrete, with the study finding that resistivity growth levels off after 21 days. These conclusions were drawn based on conventional concrete, but the composition of conventional concrete and UHPC matrices differs significantly, and the mechanism by which conductive phases affect the mechanical properties of conventional concrete cannot be directly applied to UHPC. While the electrical conductivity of conventional concrete typically stabilizes within 28 days, this decay pattern may vary in UHPC.

[0005] Therefore, how to reasonably select conductive phases of different materials, dosages, and sizes for co-mixing with steel fibers, maximize the positive mixing effect and size effect of each conductive phase to greatly enhance the connectivity of the conductive network, and determine the attenuation law of the conductive performance of conductive UHPC with age, is of great value to the application of conductive UHPC. Summary of the Invention

[0006] The purpose of the present invention is to provide a conductive three-phase ultra-high performance concrete and a preparation method thereof, by adding steel fiber, carbon fiber and conductive nano-carbon black into the concrete to take into account the construction performance, mechanical properties and electrothermal properties of the concrete.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a conductive three-phase ultra-high performance concrete comprising the following components: steel fiber, carbon fiber, conductive nano-carbon black, cement, silica fume, fly ash, fine aggregate, water reducer, hydrolyzed silane solution, and water;

[0009] The conductive three-phase ultra-high performance concrete contains 1.6-2.5 vol.% steel fiber and 0.6-1.0 vol.% carbon fiber. The conductive nano-carbon black accounts for 0.7-1.0 wt.% of the total mass of cement, silica fume and fly ash.

[0010] Preferably, the conductive three-phase ultra-high performance concrete has a steel fiber content of 2.0-2.5 vol.%, a carbon fiber content of 0.6-0.8 vol.%, and a conductive nano-carbon black content of 0.7-0.85 wt.% of the total weight of cement, silica fume, and fly ash.

[0011] Preferably, the steel fiber content in the conductive three-phase ultra-high performance concrete is 2.0 vol.%, and the carbon fiber content is 0.8 vol.%; the mass of the conductive nano-carbon black is 0.7 wt% of the sum of the mass of cement, silica fume and fly ash.

[0012] Preferably, it includes the following components: cement 800-900 kg·m -3 Silica fume 170~190kg·m -3 、Fly ash 110~130kg·m -3 , fine aggregate 920~950kg·m -3 , water reducing agent 29~35kg·m -3 , hydrolyzed silane solution 19~25kg·m -3 , water 220~240kg·m -3 , steel fiber, carbon fiber, conductive nano carbon black.

[0013] Preferably, the steel fiber has a length of 8 to 18 mm, a diameter of 0.12 to 0.3 mm, and a density of 7800 to 8000 kg·m -3 , tensile strength is 2.0~3Gpa, and elastic modulus is 200~210Gpa.

[0014] Preferably, the carbon fiber has a diameter of 7-10 μm, a tensile strength of 3.6-3.8 GPa, an elastic modulus of 220-240 GPa, an elongation at break of 1.5-2%, and a density of 1760-1770 kg·m -3 .

[0015] Preferably, the conductive nano carbon black has a particle size of 40 to 50 nm and a specific surface area of ​​6×10 4 ~8×10 4 m 2 kg -1 , density is 120~130kg·m -3 .

[0016] Preferably, the fine aggregate comprises a mixture of 26-40 mesh quartz sand, 70-120 mesh quartz sand and quartz powder; the mesh number of the quartz powder is ≥325 mesh, and the mass ratio of 26-40 mesh quartz sand, 70-120 mesh quartz sand and quartz powder is (0.1-0.3):(0.6-1):(0.3-0.5).

[0017] Preferably, the hydrolyzed silane solution is prepared by mixing KH550, water and anhydrous ethanol in a mass ratio of (1-2):(3-4):(2.5-4).

[0018] Preferably, the cement is P·O 52.5 Portland cement or P·O 42.5 Portland cement;

[0019] The mass content of SiO2 in the silica fume is 95.7-99%;

[0020] The fly ash particle size is first-grade fly ash;

[0021] The water reducer is a polycarboxylate water reducer.

[0022] In a second aspect, the present invention further provides a method for preparing the conductive three-phase ultra-high performance concrete, comprising the following steps:

[0023] Mixing cement, silica fume, fly ash and fine aggregate to obtain a first mixture;

[0024] Adding carbon fiber to 30-35% by mass of water, stirring, and ultrasonically dispersing to obtain a carbon fiber dispersion;

[0025] Adding conductive nano-carbon black to 30-35% by mass of water, stirring, and ultrasonically dispersing to obtain a conductive nano-carbon black dispersion;

[0026] The remaining water, water reducer, hydrolyzed silane solution, carbon fiber dispersion, and conductive nano carbon black dispersion are added to the first mixture and stirred, and then steel fiber is added and stirred continuously to obtain conductive three-phase ultra-high performance concrete.

[0027] The conductive three-phase ultra-high performance concrete and its preparation method of the present invention have the following beneficial effects over the prior art:

[0028] 1. The conductive three-phase ultra-high performance concrete of the present invention is prepared by adding steel fiber, carbon fiber, and conductive nano-carbon black into the concrete. When the steel fiber content is 1.6-2.5 vol.%, the carbon fiber content is 0.6-1.0 vol.%, and the conductive nano-carbon black content is 0.7-1.0 wt.% of the total weight of cement, silica fume, and fly ash, the concrete has good construction performance, mechanical properties, and electrical and thermal properties.

[0029] 2. The decrease in expansion and change in mechanical properties caused by the blending of the conductive three-phase steel fiber, carbon fiber, and conductive nano-carbon black can be approximately regarded as the superposition of the effects of each individual doping (slightly less than the superposition). The decrease in resistivity caused by the blending of the conductive three-phase is much greater than the difference between the resistance of the UHPC matrix, the resistance of the three conductive phases doped separately, and the parallel resistance of the UHPC matrix, indicating that the complementary size effects of the three significantly enhance the connectivity of the conductive network.

[0030] 3. The optimal SSF content of the conductive three-phase of the present invention is 2.0 vol.%, CF content is 0.8 vol.%, and CNCB content is 0.7 wt%. The resistivity of the three-phase conductive optimal mixed UHPC at the 28-day age is 99.85% lower than that of the plain UHPC. The resistivity hardly increases after the 7-day age. The temperature rises by 54.9°C after 150 minutes of power-on, showing good application prospects for de-icing and snow melting. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] To more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments of the present invention. Those skilled in the art can also derive other drawings based on these drawings without inventive effort.

[0032] Figure 1 is the effect curve of the conductive phase content on the expansion;

[0033] Figure 2 is the effect curve of the conductive phase content on compressive strength;

[0034] Figure 3 This is the effect curve of the conductive phase content on the tensile strength;

[0035] Figure 4 is the effect curve of the conductive phase content on resistivity;

[0036] Figure 5 The influence of conductive phase material on the expansion of UHPC and its change rate;

[0037] Figure 6 The test results of compressive strength and tensile strength of UHPC with five mix ratios in Example 8 and Comparative Examples 1 to 4 are as follows;

[0038] Figure 7 The microscopic effects of the conductive phase materials on the mechanical properties of UHPC in Comparative Examples 1 to 4 are shown;

[0039] Figure 8 The resistivity of UHPC with the five mix ratios in Example 8 and Comparative Examples 1 to 4 changes with age after standard curing for 1 day, 3 days, 7 days, 14 days and 28 days;

[0040] Figure 9 It is the conductive path formed by SSF, CF, and CNCB conductive phase materials in UHPC;

[0041] Figure 10 Schematic diagram of the development of the conductive path of three-phase conductive UHPC;

[0042] Figure 11 This is a top view of the electrothermal performance test points;

[0043] Figure 12 The effects of the conductive phase materials in the five mix ratios in Example 8 and Comparative Examples 1 to 4 on the electrothermal properties of UHPC. DETAILED DESCRIPTION

[0044] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0045] It should be noted that the order of description of the following embodiments is not intended to limit the preferred order of the embodiments. In addition, in the description of this application, the term "including" means "including but not limited to". Various embodiments of the present invention may be in the form of a range; it should be understood that the description in the form of a range is merely for convenience and brevity and should not be understood as a rigid limitation on the scope of the invention; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the numbered ranges, such as 1, 2, 3, 4, 5 and 6, regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited numbers (fractions or integers) within the indicated range.

[0046] The present application provides a conductive three-phase ultra-high performance concrete, comprising the following components: steel fiber, carbon fiber, conductive nano-carbon black, cement, silica fume, fly ash, fine aggregate, water reducer, hydrolyzed silane solution, and water;

[0047] The steel fiber content in the conductive three-phase ultra-high performance concrete is 1.6-2.5 vol.%, the carbon fiber content is 0.6-1.0 vol.%, and the conductive nano-carbon black mass is 0.7-1.0 wt.% of the sum of the mass of cement, silica fume and fly ash.

[0048] In some embodiments, preferably, the steel fiber content in the conductive three-phase ultra-high performance concrete is 2.0-2.5 vol.%, and the carbon fiber content is 0.6-0.8 vol.%; the mass of the conductive nano-carbon black is 0.7-0.85 wt.% of the sum of the mass of cement, silica fume and fly ash; more preferably, the steel fiber content in the conductive three-phase ultra-high performance concrete is 2.0 vol.%, and the carbon fiber content is 0.8 vol.%; the mass of the conductive nano-carbon black is 0.7 wt.% of the sum of the mass of cement, silica fume and fly ash.

[0049] In some embodiments, the conductive three-phase ultra-high performance concrete comprises the following components: cement 800-900 kg·m -3 Silica fume 170~190kg·m -3 、Fly ash 110~130kg·m -3 , fine aggregate 920~950kg·m -3 , water reducing agent 29~35kg·m -3 , hydrolyzed silane solution 19~25kg·m -3 , water 220~240kg·m -3 , steel fiber, carbon fiber, conductive nano carbon black; the steel fiber content in the conductive three-phase ultra-high performance concrete is 2.0-2.5 vol.%, and the carbon fiber content is 0.6-0.8 vol.%; if the volume of the conductive three-phase ultra-high performance concrete is 1m 3 , the steel fiber content is 2.0~2.5%m 3 , carbon fiber content is 0.6~0.8%m 3 ; Correspondingly, the mass of the steel fiber and carbon fiber added is its volume multiplied by its density. For example, the density of steel fiber is 7800kg·m -3 , the mass of steel fiber added is 156~195kg; if the density of carbon fiber is 1760kg·m -3 , the mass of carbon fiber added is 10.56~14.08kg; the mass of conductive nano carbon black added is 0.7~1.0% of the sum of the mass of cement, silica fume and fly ash.

[0050] In some embodiments, the steel fiber has a length of 8 to 18 mm, a diameter of 0.12 to 0.3 mm, and a density of 7800 to 8000 kg·m -3 , tensile strength is 2.0~3Gpa, and elastic modulus is 200~210Gpa.

[0051] In some embodiments, the carbon fiber has a diameter of 7 to 10 μm, a tensile strength of 3.6 to 3.8 GPa, an elastic modulus of 220 to 240 GPa, an elongation at break of 1.5 to 2%, and a density of 1760 to 1770 kg·m -3 .

[0052] In some embodiments, the particle size of the conductive nanocarbon black is 40 to 50 nm and the specific surface area is 6×10 4 ~8×10 4 m 2 kg -1 , density is 120~130kg·m -3 .

[0053] In some embodiments, the fine aggregate includes a mixture of 26-40 mesh quartz sand, 70-120 mesh quartz sand and quartz powder; the quartz powder has a mesh size of ≥325 mesh, and the mass ratio of 26-40 mesh quartz sand, 70-120 mesh quartz sand and quartz powder is (0.1-0.3):(0.6-1):(0.3-0.5).

[0054] In some embodiments, the hydrolyzed silane solution is prepared by mixing KH550, water, and anhydrous ethanol in a mass ratio of (1-2):(3-4):(2.5-4).

[0055] In some embodiments, the cement is P·O 52.5 Portland cement or P·O 42.5 Portland cement;

[0056] In some embodiments, the SiO2 content in the silica fume is 95.7-99% by mass, and the specific surface area of ​​the silica fume is 21800 m 2 / kg.

[0057] In some embodiments, the fly ash particle size is primary fly ash.

[0058] In some embodiments, the water reducer is a polycarboxylate water reducer.

[0059] Based on the same inventive concept, the present invention also provides a method for preparing the above-mentioned conductive three-phase ultra-high performance concrete, comprising the following steps:

[0060] Mixing cement, silica fume, fly ash and fine aggregate to obtain a first mixture;

[0061] Add carbon fiber to 30-35% mass fraction of water (i.e. 224-230 kg·m -3 30-35% of water) and stirred to obtain a carbon fiber dispersion;

[0062] Adding conductive nano-carbon black to 30-35% by mass of water and stirring to obtain a conductive nano-carbon black dispersion;

[0063] The remaining water, water reducer, hydrolyzed silane solution, carbon fiber dispersion, and conductive nano carbon black dispersion are added to the first mixture and stirred, and then steel fiber is added and stirred continuously to obtain conductive three-phase ultra-high performance concrete.

[0064] In some embodiments, a method for preparing conductive three-phase ultra-high performance concrete comprises the following steps:

[0065] S1. Add cement, silica fume, fly ash and fine aggregate into a mixer and stir for 3 minutes to obtain a first mixture;

[0066] S2, add carbon fiber to 1 / 3 of the mass of water (i.e. 224-230 kg·m -3 The mixture was added to 1 / 3 of water, stirred for 10 min, and then ultrasonically dispersed for 10 min to obtain a carbon fiber dispersion;

[0067] S3, add conductive nano carbon black to 1 / 3 of the mass of water (i.e. 224-230 kg·m -3 The mixture was added to 1 / 3 of water, stirred for 10 min, and then ultrasonically dispersed for 10 min to obtain a conductive nano-carbon black dispersion;

[0068] S4. Add the remaining 1 / 3 of the mass of water, water reducer, hydrolyzed silane solution, carbon fiber dispersion, and conductive nano-carbon black dispersion to the first mixture, stir for 5 minutes, then add steel fiber, and continue stirring for 6 to 7 minutes to obtain conductive three-phase ultra-high performance concrete.

[0069] The following further illustrates the conductive three-phase ultra-high performance concrete and its preparation method of the present application with specific examples. This section further illustrates the present invention with reference to specific examples, but should not be construed as limiting the present invention. Unless otherwise specified, the technical means employed in the examples are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods, and equipment employed in the present invention are conventional in the art.

[0070] In the following examples, the steel fibers used were straight copper-plated steel fibers produced by Ganzhou Daye Metal Fiber Co., Ltd., with a length of 13 mm, a diameter of 0.2 mm, and a density of 7800 kg·m -3 , tensile strength is 2.8Gpa, elastic modulus is 205Gpa, resistivity is <5×10 -4 Ω·cm;

[0071] The carbon fiber used is T300 chopped carbon fiber produced by Polysun Carbon Fiber (Guangdong) Co., Ltd., with a length of 6mm, a diameter of 7μm, a tensile strength of 3.6Gpa, an elastic modulus of 220Gpa, an elongation at break of 1.5%, and a density of 1760kg·m -3 , resistivity <1×10 -3 Ω·cm;

[0072] The conductive nanocarbon black manufacturer is Tianjin Huacai Chemical Co., Ltd., with a particle size of 40nm and a specific surface area of ​​6×10 4m 2 kg -1 , density is 120kg·m -3 , resistivity <1×10 -1 Ω·cm.

[0073] Example 1

[0074] The present invention provides a conductive three-phase ultra-high performance concrete, comprising the following components: cement 874 kg·m -3 Silica fume 175kg·m -3 、Fly ash 116kg·m -3 , fine aggregate 932kg·m -3 , water reducing agent 29kg·m -3 、Hydrolyzed silane solution 19kg·m -3 , water 224kg·m -3 , steel fiber, carbon fiber, conductive nano carbon black;

[0075] The conductive three-phase ultra-high performance concrete contains 1.6 vol.% steel fiber and 0.6 vol.% carbon fiber. The conductive nano-carbon black accounts for 0.7 wt.% of the total mass of cement, silica fume, and fly ash.

[0076] The fine aggregate includes a mixture of 26-mesh quartz sand, 70-mesh quartz sand and quartz powder; the quartz powder has a mesh size of 400 mesh, and the mass ratio of 26-mesh quartz sand, 70-mesh quartz sand and quartz powder is 0.1:0.6:0.3;

[0077] The hydrolyzed silane solution was prepared by mixing KH550 (γ-aminopropyltriethoxysilane), water, and anhydrous ethanol in a mass ratio of 1:3:2.5;

[0078] The cement is P·O 52.5 Portland cement;

[0079] The SiO2 mass content in silica fume is 95.7%, and the specific surface area of ​​silica fume is 21800m 2 / kg;

[0080] The fly ash particle size is first-grade fly ash;

[0081] The water reducer is a polycarboxylic acid water reducer, specifically a polycarboxylic acid high performance water reducer MT-3601P, which was purchased from Guangzhou Mok Building Materials Technology Co., Ltd.

[0082] The method for preparing the conductive three-phase ultra-high performance concrete comprises the following steps:

[0083] S1. Add cement, silica fume, fly ash and fine aggregate into a mixer and stir for 3 minutes to obtain a first mixture;

[0084] S2, add carbon fiber to 1 / 3 of the mass of water (i.e. 224kg·m -3 The mixture was added to 1 / 3 of water, stirred for 10 min, and then ultrasonically dispersed for 10 min to obtain a carbon fiber dispersion;

[0085] S3, add conductive nano carbon black to 1 / 3 of the mass of water (i.e. 224kg·m -3 The mixture was added to 1 / 3 of water, stirred for 10 min, and then ultrasonically dispersed for 10 min to obtain a conductive nano-carbon black dispersion;

[0086] S4. Add the remaining 1 / 3 of the mass of water, water reducer, hydrolyzed silane solution, carbon fiber dispersion, and conductive nano-carbon black dispersion to the first mixture, stir for 5 minutes, then add steel fiber and continue stirring for 7 minutes to obtain conductive three-phase ultra-high performance concrete.

[0087] Based on Example 1, the applicant conducted an orthogonal experiment, which included the following Examples 2 to 9 and Comparative Example 1. Specifically, the ultra-high performance concrete components in Examples 2 to 9 and Comparative Example 1 were the same as in Example 1, except that the steel fiber content, carbon fiber content, and conductive nano-carbon black content were different from those in Example 1, and the rest were the same as in Example 1.

[0088] The specific proportions of the components of the ultra-high performance concrete in Examples 2 to 9 and Comparative Example 1 are shown in Table 1 below.

[0089] Table 1 - Proportions of components in orthogonal test

[0090]

[0091]

[0092] In Table 1, SSF represents steel fiber, CF represents carbon fiber, CNCB represents conductive nanocarbon black, OPC represents cement, SF represents silica fume, FA represents fly ash, QS represents fine aggregate, SP represents water reducing agent, GW represents hydrolyzed silane solution, and W represents water.

[0093] Furthermore, the applicant also conducted comparative experiments 2 to 4 by adding only one of steel fiber, carbon fiber, and conductive nano-carbon black to ultra-high performance concrete; specifically, the ultra-high performance concrete in comparative examples 2 to 4 is the same as that in Example 1, except that the steel fiber content, carbon fiber content, and conductive nano-carbon black content are different from those in Example 1, and the rest are the same as those in Example 1, as shown in Table 2 below.

[0094] Table 2 - Distribution ratio of each group of ultra-high performance concrete in comparative examples 2 to 4

[0095]

[0096] Performance Testing

[0097] According to the above Examples 1 to 9, the method in Comparative Example 1 was used to obtain conductive three-phase ultra-high performance concrete; then, according to the "Standard for Test Methods for Performance of Ordinary Concrete Mixtures" (GB / T 20080-2016), the expansion of UHPC was measured using a slump cone and an expansion plate.

[0098] According to the above examples 1 to 9, the method in comparative example 1 was used to obtain conductive three-phase ultra-high performance concrete, and a 100mm×100mm×100mm cubic compression test piece, a 368mm×50mm×50mm tensile bone test piece, and a 100mm×100mm×400mm conductive performance test piece (electrical thermal performance test piece) were cast; after the mixture of each test piece was placed in a mold, it was vibrated until slurry came out of the surface; when the conductive performance test piece was molded, a copper mesh was inserted into the mold. After the test piece was made, it was immediately placed in a standard curing room and standard cured for 48 hours at (20±2)°C and a relative humidity of ≥95% before demolding. After demolding, the mechanical performance test piece was steam cured at 95°C±5°C for 48 hours. After the test piece cooled to room temperature, it was cured according to the method of "Reactive Powder Concrete" (GB / T Compressive strength was measured according to T / CBMF37-2018 and T / CCPA7-2018, "Basic Properties and Test Methods of Ultra-High Performance Concrete." Conductivity tests for orthogonal testing were conducted on specimens removed from the formwork and cured to 28 days. Resistivity tests were conducted on specimens removed from the formwork and cured to 1, 3, 7, 14, and 28 days. With the exception of expansion, each physical quantity for the same UHPC mix was tested on three specimens. Unless otherwise specified, values ​​are the average of the three specimens, and the coefficient of variation is also provided.

[0099] The test method for conductivity or resistivity is: use the four-electrode method to test, control the input voltage to 30V through a single-phase isolation voltage regulator, use a digital multimeter to measure current and voltage, and calculate the resistivity according to the following formula.

[0100]

[0101] Where: ρ is the resistivity of the specimen (Ω·cm); R is the resistance value of the specimen (Ω); S is the energized area of ​​the specimen (cm 2 ), in this embodiment, S is 100cm 2 ; L is the distance between the two electrodes (cm), in this embodiment L is 10cm; U is the measured voltage (V); I is the measured current (A).

[0102] The microstructure of each UHPC was tested by breaking the steam-cured specimens into small pieces and soaking them in anhydrous ethanol for 48 hours to terminate the hydration reaction. After the hydration reaction, the specimens were dried in a drying oven. After drying, the specimens were removed and the microscopic distribution of the conductive phases was imaged using a scanning electron microscope (SEM).

[0103] The properties of the conductive three-phase ultra-high performance concrete in Examples 1 to 9 and Comparative Example 1 are shown in Table 3 below.

[0104] Table 3 - Properties of conductive three-phase ultra-high performance concrete in Examples 1 to 9 and Comparative Example 1

[0105]

[0106] Note: When the spread is >650mm, the flowability meets self-leveling requirements; when it is >500mm, the flowability is good. μ is the mean value; Cv is the coefficient of variation, which is the ratio of the standard deviation to the mean, expressed as a percentage.

[0107] The orthogonal test results in Table 3 were subjected to range analysis and variance analysis, and the results are shown in Table 4. As shown in Table 4, the range analysis results are highly consistent with the variance analysis results, and the influence of each factor on the mechanical and electrical properties of three-phase conductive UHPC is ranked in the same order. For the compressive strength of three-phase conductive UHPC, SSF > CNCB > CF, and for the tensile strength, CF > SSF > CNCB. The influence of SSF and CF on mechanical properties is primarily reflected in the strengthening effect of the bridging effect between SSF and CF, while the influence of CNCB on mechanical properties is reflected in the weakening effect of CNCB after incorporation.

[0108] For three-phase conductive UHPC resistivity, CNCB > SSF > CF. In orthogonal experiments, CF and SSF began to significantly reduce the UHPC resistivity, indicating that the conductive pathway formed by the fibers has approached the percolation threshold and has been initially improved. However, CNCB still has room for improvement in reducing the UHPC matrix resistance.

[0109] Table 4 - Orthogonal test range and variance analysis results

[0110]

[0111] Note: R, factor range; α, significance.

[0112] According to the orthogonal test results in Table 3, the effect curves of the average compressive strength, average tensile strength and average resistivity at the same level of each factor are drawn as the factor level changes, as shown in the figure. Figures 1 to 4 shown.

[0113] Depend on Figures 1 to 4It can be seen that when the SSF content increases from 1.6 vol.% to 1.8 vol.% and then to 2.0 vol.%, the average UHPC expansion first decreases by 4.73% and then decreases by 4.30%, the average compressive strength first increases by 3.46% and then increases by 11.68%, the average tensile strength first increases by 1.60% and then increases by 0.77%, and the average resistivity first decreases by 2.42% and then decreases by 34.41%. When the CF content increases from 0.6 vol.% to 0.8 vol.% and then to 1.0 vol.%, the average UHPC expansion first decreases by 4.15% and then decreases by 1.67%. The average compressive strength first increased by 3.8% and then increased by 0.02%, the average tensile strength first increased by 8.11% and then decreased by 1.77%, and the average resistivity first decreased by 17.33% and then decreased by 11.86%; when the nano-carbon black content increased from 0.7wt% to 0.85wt% and then to 1.0wt%, the average UHPC expansion first decreased by 5.23% and then decreased by 10.71%, the average compressive strength first decreased by 1.39% and then decreased by 0.63%, the average tensile strength first decreased by 1.39% and then decreased by 0.63%, and the average resistivity first decreased by 41.72% and then decreased by 31.93%.

[0114] This indicates that within the range of levels of each factor in the orthogonal experiment, the addition of all three types of conductive phase materials results in a decrease in UHPC expansion and an increase in electrical conductivity, but CNCB has the most significant impact. The SSF content has the most significant effect on UHPC mechanical properties, reaching its maximum at the third level, which can be 2.0 vol.%. At the second level, CF exhibits optimal mechanical properties, and further increases in mechanical properties slow the decrease in resistivity, leading to the formation of clumping during mixing, which can be achieved at 0.8 vol.%. When the SSF content is 2.0 vol.%, the CF content is 0.8 vol.%, and the CNCB content is 0.7 wt.%, the UHPC expansion is only 510 mm, close to the lower limit of good fluidity (500 mm). Therefore, the optimal conductive three-phase hybrid UHPC content is 2.0 vol.% SSF, 0.8 vol.%, and 0.7 wt.% CNCB.

[0115] Mechanism for achieving UHPC performance through optimal mixing of three conductive phases

[0116] Considering the one-sidedness of the optimal conductive phase mixing ratio revealed by the orthogonal experiment in achieving the performance mechanism of UHPC, based on the optimal mixing ratio of each conductive phase material, performance tests were conducted on five mix ratios (hereinafter referred to as the above five mix ratios): plain UHPC without conductive phase material (i.e., Comparative Example 1), SSF-UHPC doped with 2.0 vol.% SSF alone (i.e., Comparative Example 2), CF-UHPC doped with 0.8 vol.% CF alone (i.e., Comparative Example 3), CB-UHPC doped with 0.7 wt.% CNCB alone (i.e., Comparative Example 4), and a three-phase conductive UHPC doped with these three conductive phase materials (2.0 vol.% SSF, 0.8 vol.% CF, and 0.7 wt.% CNCB, i.e., Example 8). The effects of single and mixed mixing of each conductive phase on UHPC performance were analyzed to further reveal the mechanism for achieving the optimal mixing performance of UHPC.

[0117] Figure 5 is the influence of conductive phase material on UHPC expansion and its change rate, Figure 5 In the figures, plain UHPC represents comparative example 1, SSF-UHPC represents comparative example 2, CF-UHPC represents comparative example 3, CB-UHPC represents comparative example 4, and three-phase UHPC represents embodiment 8.

[0118] Depend on Figure 5 It can be seen that the expansion of plain UHPC (i.e., Comparative Example 1), UHPC with 2.0 vol.% SSF (i.e., Comparative Example 2), UHPC with 0.8 vol.% CF (i.e., Comparative Example 3), UHPC with 0.7 wt.% CNCB (i.e., Comparative Example 4), and UHPC blended with 2.0 vol.% SSF, 0.8 vol.% CF, and 0.7 wt.% CNCB (i.e., Example 8) are 820 mm, 735 mm, 710 mm, 642.5 mm, and 510 mm, respectively. This shows that the addition of all three materials leads to a decrease in expansion, but CNCB causes the most significant decrease in expansion. The expansion mechanism of SSF and CF is similar. The mechanical friction caused by fiber contact and the mechanical interlocking between the fiber networks both increase the difficulty of dispersing the UHPC mixture. The larger specific surface area of ​​CNCB significantly increases the total specific surface area of ​​the slurry particles, reducing the average water film thickness and strengthening the inter-particle forces. Furthermore, the micro-aggregate effect of CNCB causes cement particles to be encapsulated by CNCB particles, further reducing the cement paste and significantly reducing the UHPC expansion. The expansion reduction caused by the blend of the three was 310 mm, slightly lower than the combined expansion reduction of 372.5 mm caused by the individual additions.

[0119] Effects of conductive three-phase single and mixed additions on the mechanical properties of UHPC

[0120] The test results of the compressive strength and tensile strength of UHPC with five mix ratios in Example 8 and Comparative Examples 1 to 4 are shown in Figure 6 ; Figure 6 In the figures, plain UHPC represents comparative example 1, SSF-UHPC represents comparative example 2, CF-UHPC represents comparative example 3, CB-UHPC represents comparative example 4, and three-phase UHPC represents embodiment 8.

[0121] from Figure 6 As can be seen from the data, the compressive and tensile strengths of UHPC increased when SSF or CF were added alone, while the strength decreased when CNCB was added alone. SSF-UHPC achieved a 39.0 MPa increase in compressive strength and a 5.1 MPa increase in tensile strength compared to plain UHPC. CF-UHPC achieved a 22.4 MPa increase in compressive strength and a 2.2 MPa increase in tensile strength compared to plain UHPC. CB-UHPC achieved a 13.1 MPa decrease in compressive strength and a 0.94 MPa decrease in tensile strength compared to plain UHPC.

[0122] like Figure 7 As shown, it is the microscopic influence of the conductive phase material on the mechanical properties of UHPC in Comparative Examples 1 to 4, and the testing method is the same as the above-mentioned UHPC microstructure testing method.

[0123] from Figure 7 It can be seen that both SSF and CF high-strength and high-modulus fibers can form a bridging effect, inhibiting the generation of cracks and slowing down the crack propagation rate; at the same time, they transfer stress to the uncracked areas, thereby enhancing the integrity of UHPC ( Figure 7 (a, b)). The agglomeration of CNCB hinders the continuity of the matrix, increases the matrix pores, and causes defects in the internal structure of UHPC, resulting in a decrease in mechanical properties ( Figure 7 (c)); In addition, the micro-aggregate effect of CNCB will also cause it to be adsorbed on cement particles, hindering the hydration reaction of cement particles, resulting in a decrease in the strength of UHPC caused by the reduction of hydration products ( Figure 7 (d)).

[0124] The sum of the changes in UHPC compressive strength caused by the single addition of SSF, CF, and CNCB is increased by 48.3 MPa, and the sum of the changes in tensile strength is increased by 6.36 MPa.

[0125] Effects of single and mixed conductive phase additions on the electrical conductivity of UHPC

[0126] The test results of the UHPC electrical conductivity of the five mix ratios in Example 8 and Comparative Examples 1 to 4 at standard curing for 1d, 3d, 7d, 14d and 28d are as follows: Figure 8 . Figure 8In the figures, plain UHPC represents comparative example 1, SSF-UHPC represents comparative example 2, CF-UHPC represents comparative example 3, CB-UHPC represents comparative example 4, and three-phase UHPC represents embodiment 8.

[0127] Depend on Figure 8 It can be seen that the resistivity of each group increases with the increase of curing age. This can be explained from the UHPC conductive mechanism. There are three main conductive modes of conductive UHPC: (1) ionic conduction, under the action of external electric field, the free ions Ca in the pores 2+ 、Na + , K + OH - (1) The current generated by the directional movement of free electrons in the material under the action of an external electric field; (2) Electronic conduction, the current generated by the directional movement of free electrons in the material under the action of an external electric field; (3) Hole conduction, the current generated by the electrons breaking through the potential barrier and migrating in the holes. At a young age, the degree of hydration of UHPC is low, and the free water content in the matrix pores is rich. The abundant water acts as an excellent carrier for ion migration, greatly reducing the resistance of the UHPC matrix. As the age progresses, the hydration reaction of UHPC continues, the free water in the matrix is ​​consumed, and the aqueous solution in the pores is gradually replaced by hydration products, and the ionic conductivity is weakened. Therefore, the resistivity of each group increases to varying degrees with the increase of age.

[0128] The resistivity of plain UHPC and SSF-UHPC increases significantly with age. The resistivity of plain UHPC increases from 4.91×10 3 Ω·cm increased to 4.22×10 at 28 days old. 5 Ω·cm, the resistivity of SSF-UHPC increased from 3.61×10 3 Ω·cm increased to 1.82×10 at 28 days old 5 Ω·cm. The resistivity of both groups increased significantly during the curing period, indicating that ionic conductivity significantly influences their resistivity. Although SSF-UHPC contains SSF, the SSF does not form a dense, overlapping, and conductive SSF network, so the conductivity pattern is still significantly influenced by ionic conductivity. Although the addition of SSF reduces the resistivity of 28-day-old SSF-UHPC by 56.83% compared to plain UHPC of the same age, the resistivity still increases significantly with age.

[0129] The resistivity of CF-UHPC and CB-UHPC slowed down significantly with the increase of age and the resistivity decreased significantly. The resistivity of CF-UHPC increased from 1.93×10 3 Ω·cm increased to 8.36×10 at 28 days old. 3 Ω·cm, the resistivity of CB-UHPC is 7.17×10 2Ω·cm increased to 1.18×10 4 Ω·cm. This indicates that the weight of the influence of ionic conduction on resistivity decreases, and the conduction mode begins to shift from ionic conduction to CF pathway conduction and CNCB pathway conduction. The resistivity of CF-UHPC is more stable with age than that of CB-UHPC. This is because, in CB-UHPC, as the hydration reaction proceeds, the hydration products will separate the originally adjacent or contacting CNCB particles, increasing the distance between them and weakening the tunnel effect, which reduces the short-range conductivity of CNCB. However, once the CF in CF-UHPC overlaps with each other to form a network, electrons move through the fiber network. Even if the surface is covered with hydration products, it will not affect the movement of electrons inside the fiber.

[0130] Figure 9 Conductive pathways formed by SSF, CF, and CNCB conductive phase materials in UHPC

[0131] The resistivity of three-phase conductive UHPC is 5.01×10 2 Ω·cm increased to 6.52×10 at 28 days old. 2 Ω·cm. The resistivity at 28 days decreased by 99.85% compared to plain UHPC. The resistivity increased slowly with age, almost stopping after 7 days. The conduction mode in three-phase conductive UHPC is almost entirely electronic, with current flowing almost entirely through the conductive network formed by the conductive phase. The conductivity of the matrix is ​​negligible, indicating that the percolation threshold of the conductive phase has been reached.

[0132] According to the resistivity test results of 28d-old UHPC, SSF-UHPC, CF-UHPC and CB-UHPC, according to the resistance calculation principle of parallel circuit The resistivity of the SSF network, the resistivity of the CF network, and the resistivity of the CNCB network in UHPC can be calculated to be 3.20×10 5 Ω·cm、1.21×10 4 Ω·cm and 8.53×10 3 Ω·cm; the resistivity calculated by connecting the four in parallel is 4.87×10 3 Ω·cm, which is 7.48 times the measured resistivity of three-phase conductive UHPC at 28 days of age. This shows that three-phase conductive UHPC cannot be regarded as a parallel connection of four components. Instead, the conductive three-phase material greatly enhances the connectivity of the conductive network due to the size effect, forming a conductive network with greatly reduced resistance. SSF is evenly distributed in the matrix, initially forming a millimeter-scale fiber conductive framework, which initially reduces the overall resistivity of UHPC. Specifically, Figure 9 It is the conductive path formed by SSF, CF, and CNCB conductive phase materials in UHPC; Figure 9It can be seen that the introduction of CF not only forms a micron-scale CF conductive network ( Figure 9 (a)), and many CFs are located in the gaps of the millimeter-scale conductive framework formed by SFF, further enhancing the connectivity of the SSF fiber conductive framework (conductive network); CNCB particles are uniformly distributed in the UHPC matrix ( Figure 9 (b)) not only effectively reduces the potential barrier between matrix materials, but also further enhances the connectivity and tunneling effect between fiber networks. The incorporation of the above three conductive phases not only takes advantage of the large aspect ratio and easy overlap of SSF and CF, but also gives play to the short-range conductive characteristics of CNCB, forming a composite spatial conductive network with SSF as the main frame, CF as auxiliary branches, and nanocarbon black as the matrix filling ( Figure 9 (c)), the resistivity of UHPC decreases exponentially and the age stability is significantly improved.

[0133] Further, Figure 10 Schematic diagram of the development of three-phase conductive UHPC conductive path; Figure 10 It can be seen that carbon fibers are distributed in the gaps between steel fibers, and nano-carbon black is distributed in the gaps between carbon fibers. The maximum net distance and the sum of the net distances between these good conductors are greatly reduced, thereby greatly reducing the resistance (electrical resistance) to electron flow (movement).

[0134] Electrothermal performance of conductive three-phase optimal mixed UHPC and their respective single-phase UHPC

[0135] The inherent mechanism of UHPC's electric heating is to convert electrical energy into thermal energy. At the microscopic level, due to the existence of resistance inside the conductive path, electrons collide with atoms in the path during the flow, resulting in energy loss and conversion into thermal energy. Although, when the voltage is constant, the power consumption (heat energy generated) is inversely proportional to the resistance. However, in order to intuitively show the engineering effects of using the five mix ratios of UHPC in Example 8 and Comparative Examples 1 to 4 in melting snow on the bridge deck after power is applied, this article also uses the above five mix ratios of UHPC that have been cured for 28 days to make 100mm×100mm×400mm conductive performance test pieces for electric heating performance tests. As Figure 11 The test method is as follows: Wrap the specimen with a 1.5 cm thick thermal insulation foam board and place the specimen at both ends ( Figure 11 The copper mesh AA' and copper mesh DD' in the test piece are connected to a 30V AC voltage, and the temperature of each measuring point on the surface of the test piece is measured every ten minutes (see the test point for details). Figure 11 The test area of ​​BB'CC' formation, Figure 11 1, 2, 3, 4, 5, 6, 7, 8, 9, Figure 11The units in the figure are all mm). The average temperature of 9 measuring points is used as the specimen temperature. The temperature variation curves of UHPC with five mix ratios (single doping, mixed doping and no doping) according to the optimal mixing amount of conductive phase are obtained as a function of power-on time. Figure 12 shown. Figure 12 In the figures, plain UHPC represents comparative example 1, SSF-UHPC represents comparative example 2, CF-UHPC represents comparative example 3, CB-UHPC represents comparative example 4, and three-phase UHPC represents embodiment 8.

[0136] Depend on Figure 12 As can be seen, for both the plain UHPC and SSF-UHPC specimens, there was no significant temperature change after power was applied, with the temperature variation within the specimens less than 2°C (which can be considered an error caused by the environment). For the CB-UHPC specimen, heat generation and heat exchange losses reached equilibrium after 110 minutes of power application, resulting in a temperature increase of 7.1°C. The CF-UHPC specimen reached heat exchange equilibrium after 90 minutes of power application, ultimately increasing in temperature by 9.1°C. The three-phase conductive UHPC specimen had an initial temperature of 16.1°C and rose to 71.0°C after 150 minutes of power application (with a surface temperature difference of less than 2°C), a 54.9°C increase, with the temperature continuing to rise slowly.

[0137] The above are merely preferred embodiments of the present application and only specifically describe the technical principles of the present application. These descriptions are intended only to explain the principles of the present application and should not be construed in any way as limiting the scope of protection of the present application. Based on the explanations herein, any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present application, as well as other specific implementations of the present application that can be conceived by those skilled in the art without inventive effort, shall be included within the scope of protection of the present application.

Claims

1. A conductive three-phase ultra-high performance concrete, characterized in that: It includes the following components: steel fiber, carbon fiber, conductive nano carbon black, cement, silica fume, fly ash, fine aggregate, water reducing agent, hydrolyzed silane solution, water; The conductive three-phase ultra-high performance concrete contains 1.6-2.5 vol.% steel fiber and 0.6-1.0 vol.% carbon fiber. The conductive nano-carbon black accounts for 0.7-1.0 wt.% of the total mass of cement, silica fume and fly ash.

2. The conductive three-phase ultra-high performance concrete according to claim 1, characterized in that: The conductive three-phase ultra-high performance concrete has a steel fiber content of 2.0-2.5 vol.%, and a carbon fiber content of 0.6-0.8 vol.%. The conductive nano-carbon black is 0.7-0.85 wt.% of the total weight of cement, silica fume, and fly ash. Preferably, the steel fiber content in the conductive three-phase ultra-high performance concrete is 2.0 vol.%, and the carbon fiber content is 0.8 vol.%; the mass of the conductive nano-carbon black is 0.7 wt% of the sum of the mass of cement, silica fume and fly ash.

3. The conductive three-phase ultra-high performance concrete according to claim 1, characterized in that: Includes the following components: cement 800-900 kg·m -3 Silica fume 170~190kg·m -3 、Fly ash 110~130kg·m -3 , fine aggregate 920~950kg·m -3 , water reducing agent 29~35kg·m -3 , hydrolyzed silane solution 19~25kg·m -3 , water 220~240kg·m -3 , steel fiber, carbon fiber, conductive nano carbon black.

4. The conductive three-phase ultra-high performance concrete according to claim 1, characterized in that: The steel fiber has a length of 8 to 18 mm, a diameter of 0.12 to 0.3 mm, and a density of 7800 to 8000 kg·m -3 , tensile strength is 2.0~3Gpa, and elastic modulus is 200~210Gpa.

5. The conductive three-phase ultra-high performance concrete according to claim 1, characterized in that: The carbon fiber has a diameter of 7 to 10 μm, a tensile strength of 3.6 to 3.8 GPa, an elastic modulus of 220 to 240 GPa, an elongation at break of 1.5 to 2%, and a density of 1760 to 1770 kg·m -3 .

6. The conductive three-phase ultra-high performance concrete according to claim 1, characterized in that: The particle size of the conductive nano carbon black is 40 to 50 nm and the specific surface area is 6×10 4 ~8×10 4 m 2 kg -1 , density is 120~130kg·m -3 .

7. The conductive three-phase ultra-high performance concrete according to claim 1, characterized in that: The fine aggregate includes a mixture of 26-40 mesh quartz sand, 70-120 mesh quartz sand and quartz powder; the mesh number of the quartz powder is ≥325 mesh, and the mass ratio of 26-40 mesh quartz sand, 70-120 mesh quartz sand and quartz powder is (0.1-0.3):(0.6-1):(0.3-0.5).

8. The conductive three-phase ultra-high performance concrete according to claim 1, wherein: The hydrolyzed silane solution is prepared by mixing KH550, water and anhydrous ethanol in a mass ratio of (1-2):(3-4):(2.5-4).

9. The conductive three-phase ultra-high performance concrete according to claim 1, wherein: The cement is P·O 52.5 Portland cement or P·O 42.5 Portland cement; The mass content of SiO2 in the silica fume is 95.7-99%; The fly ash particle size is first-grade fly ash; The water reducer is a polycarboxylate water reducer.

10. A method for preparing the conductive three-phase ultra-high performance concrete according to any one of claims 1 to 8, characterized in that: The following steps are involved: Mixing cement, silica fume, fly ash and fine aggregate to obtain a first mixture; Adding carbon fiber to 30-35% by mass of water, stirring, and ultrasonically dispersing to obtain a carbon fiber dispersion; Adding conductive nano-carbon black to 30-35% by mass of water, stirring, and ultrasonically dispersing to obtain a conductive nano-carbon black dispersion; The remaining water, water reducer, hydrolyzed silane solution, carbon fiber dispersion, and conductive nano carbon black dispersion are added to the first mixture and stirred, and then steel fiber is added and stirred continuously to obtain conductive three-phase ultra-high performance concrete.